Scaling up safe motherhood program at Dang district: Impact of programmatic intervention - Chaudhary, Shrawan K (Nepal Journal of Obstetrics and Gynaecology, 2014)
Introduction: Safe motherhood has been a national priority programme and this article highlights the impact of a good programmatic approach to improve safe motherhood services in a district of mid west region of Nepal. Method: Interventions included strengthening of program- Emergency Obstetric Care Services (EmOC) at district hospital and Primary Health Care Center level (basic and comprehensive), Skilled Birth Attendance (SBA) at Health Post level and Community Based Safe Motherhood interventions at community level. In addition, improved family/community practices for birth preparedness and referral of mothers through building the capacity of individuals and families to demand and utilize health services were also implemented. Results: Met need of Emergency Obstetric Care increased from 2% in 2000 to 27.58 % in 2005/06. Number of births increased in hospital from 1078 (2003/2004) to 1753 (2005/2006). Number of caesarean sections was 10 in 2003/04 whereas it has risen to 174 in 2005/06. Similar trends were noticed in other obstetric procedures such as instrumental deliveries and manual removal of placenta. There has also been a significant increase in utilization of EmOC services among the poorest castes- Dalits and Janjatis (from 6.3% in 2000/01 to 12.7% in 2003/04). Twenty four hours blood transfusion services are made available at district hospital. EmOC fund has saved the life of 676 women who utilized EmOC fund and watch group has referred total 559 women to health facilities. Conclusion: Data from Dang district suggests that if interventions are delivered simultaneously and effectively at community level and health facility level, there is definite impact on various indicators of safe motherhood program. However, frequent turnover of staff, vacant post, lack of provision of 24 hours SBA services, limited budget for construction, training and equipment supports, lack of transportation and communication in remote Village Development Committees are barriers of effective safe motherhood program. DOI: http://dx.doi.org/10.3126/njog.v3i2.10827   Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 21-25